Remarkable efficiency of phosphate removal: Ferrate(VI)-induced in situ sorption on core-shell nanoparticles - Kralchevska, Radina P; Prucek, Robert; Kolařík, Jan; Tuček, Jiří; Machala, Libor; Filip, Jan; Sharma, Virender K; Zbořil, Radek (Water research, 2016)
Despite the importance of phosphorus as a nutrient for humans and its role in ecological sustainability, its high abundance, resulting in large part from human activities, causes eutrophication that negatively affects the environment and public health. Here, we present the use of ferrate(VI) as an alternative agent for removing phosphorus from aqueous media. We address the mechanism of phosphate removal as a function of the Fe/P mass ratio and the pH value of the solution. The isoelectric point of γ-Fe2O3 nanoparticles, formed as dominant Fe(VI) decomposition products, was identified to play a crucial role in predicting their efficiency in removing of phosphates. Importantly, it was found that the removal efficiency dramatically changes if Fe(VI) is added before (ex-situ conditions) or after (in-situ conditions) the introduction of phosphates into water. Removal under in-situ conditions showed remarkable sorption capacity of 143.4 mg P per gram of ferric precipitates due to better accessibility of active surface sites on in-situ formed ferric oxides/oxyhydroxides. At pH = 6.0-7.0, complete removal of phosphates was observed at a relatively low Fe/P mass ratio (5:1). The results show that phosphates are removed from water solely by sorption on the surface of γ-Fe2O3/γ-FeOOH core/shell nanoparticles. The advantages of Fe(VI) utilization include its environmentally friendly nature, the possibility of easy separation of the final product from water by a magnetic field or by natural settling, and the capacity for successful phosphate elimination at pH values near the neutral range and at low Fe/P mass ratios.
Keywords: železité sloučeniny; železo; Water Pollutants, Chemical; fosfáty; Nanoparticles; Ferric Compounds; Phosphates; Water Purification; Iron; čištění vody; chemické látky znečišťující vodu; nanočástice